Development of a Parking System Using the High Sensitive R503 Fingerprint Sensor for Sequential Search Algorithm Based Customer Detection - Suhartono, Suhartono; Parenreng, Jumadi M; Syafriandi K, Fahri; Zain, Satria Gunawan; Suhardi, Iwan (Internet of Things and Artificial Intelligence Journal, 2023)
Today's technological developments are very sophisticated. It can be seen with various innovations in this era, from simple innovations to innovations that are trending in the world. Parking is a condition where the driver places his vehicle in a parking lot. The parking system using the Radio Frequency Identification (RFID) system has become a technology applied to parking systems, by facilitating and providing security to customers when parking, even though they have used an RFID card, the drawbacks of the system are that anyone who has an RFID card can issue the owner's vehicle another by using the same RFID card. The solution to the lack of an RFID-based parking system is by using the High Sensitive R503 Fingerprint Sensor which will make security much better than using an RFID card, by applying the Sequential Search Algorithm to detect customers in fingerprint registration applications and using the Fingerprint R503 sensor with data verification speed. average 0.78 Second to open the parking portal.